State, results and problems of spring bread wheat selection (Experimental biology, 2016)
In the article are reflected state, results and problems of spring bread wheat selection in Kazakh Scientific research Institute of Agriculture and Plant growing (KazScRIAPG). The short characteristic of developed and permitted to use in RK and in neighboring states of Central Asia and Russian Federation varieties of spring bread wheat of KazScRIAPG selection.
Keywords: spring bread wheat; selection; variety; yield; resisters to stresses; vegetation period length; yield quality.